Factors associated with the hospitalization of users referred from primary health care to follow-up in Psychosocial Care Centers in the city of São Paulo, Brazil - Sanine, Patricia Rodrigues [UNESP]; da Silva Godoi, Lídia Pereira; da Costa Rosa, Tereza Etsuko; Garcia, Érica Marvila; Belotti, Lorrayne; Campos, Rosana Teresa Onocko; Tanaka, Oswaldo Yoshimi (FapUNIFESP (SciELO), 2024)
This study evaluated factors associated with hospitalization related to the mental health of people undergoing follow-up in Psychosocial Care Centers (CAPS, in Portuguese) in the city of São Paulo, Brazil, referred from Primary Health Care (PHC). This was an evaluative study conducted with 297 individuals in 24 adult CAPS. This study analyzed the prevalence ratios (PR) and their respective 95% confidence intervals (95% CI), obtained through Poisson Regression with robust variance. A statistically significant association was found with hospitalization during follow-ups in CAPS: having health insurance and/or medical plan; waiting time between the diagnosis and the first consultation with a non-medical professional of more than seven days; not having received medical advice regarding how long to use medication; not having received a psychopharmaceutical prescription at PHC; and having a medical history of the hospitalization due to mental health. The results warn of the need to expand access to the more socially vulnerable population, in addition to a restructuring of the services in order to provide more interactive and inclusive practices geared toward the singularities of the users.
Fatores associados à internação de usuários encaminhados pela atenção primária para acompanhamento em Centros de Atenção Psicossociais do município de São Paulo, Brasil
Keywords: Community services in mental health; Health evaluation; Mental health; Mental health servi-ces; Primary health care